Apple's custom chips : a genius decision? - Busse, Meghan R. (SAGE business cases., 2022)
When Steve Jobs co-founded Apple in 1976, his philosophy was to move fast, unencumbered by norms, and take risks in search of greater rewards. His strategy was to differentiate Apple by developing high-end products that consumers craved.